The effect of regular physical activity on exercise tolerance: a school-based intervention - Sohrabi, Mohammad-Reza; Davoudi-Monfared, Esmat; Tayefi, Batool; Hajihashemi, Zahra; Sajjadi, Elaheh (Novelty in Biomedicine, 2013)
Please cite this article as: Sohrabi MR, Davoudi-Monfared E, Tayefi B, Hajihashemi Z, Sajjadi E. The effect of regular physical activity on exercise tolerance: a school-based intervention. Novel Biomed 2013;1(2):34-38. Objectives: The main purpose of this study was to assess the effects of daily physical activity on exercise tolerance ability using the six minute walk test in healthy female students. Methods: The participants in this field study were 252 healthy girls, 9-12 years old, studying in an elementary school in Tehran from March to June 2011. A three months daily physical activity protocol, with 15 minutes exercise per day, was designed as a curricular-based exercise intervention program. The six minute walk test was used as a tool to measure exercise tolerance ability before and after the intervention. Paired t-test, ANOVA and correlation tests were used when appropriate. Results: The participants, with mean age of 10.6 (SD = 1.1), formed different body mass index groups known as underweight, normal, at risk and overweight with 8.3, 60.7, 18.7, and 12.3% respectively. The mean of the distances moved along in a six minute walk test, before and after the intervention, increased from 833.4 meter to 923.3 meter , indicating 10% increase and the difference was found to be statistically significant (P<0.001). However, analysis of mean differences of the walked distances, before and after the intervention, showed no statistically significant difference for the body mass index groups (P> 0.05). Conclusion: A 15-minutes daily physical activity could enhance the exercise tolerance of school-age girls; the activity, as an easy and inexpensive form of intervention, is recommended to students.